Employability of graduates: Malaysia - Sirat, Morshidi; Lean Heng, Chan; Shuib, Munir; Abdul Rahman, Shukran; Ahmad Kamil, Seri Rahayu; Singh, Jasvir Kaur Nachatar (UNESCO Bangkok, 2012)
There is a growing international discourse on the public responsibility for higher education and its emerging roles in human and social development (GUNI, 2008). Various forums and publications have focused on how higher education institutions (HEIs) could contribute to a systematic and proactive analysis to develop critical discourses with which societies can continually reflect on their evolution for a positive social transformation. It presents as well how HEIs could strengthen their role as agents of transformation, facing both local and global challenges. This would entail the efforts in concluding their vision and mission which need to be re-oriented towards the creation and distribution of socially relevant knowledge and complex understanding of reality. Without a doubt, strengthening the social responsibility of HEIs has become an indispensable task particularly in knowledge contribution towards a harmonious global development.